Charge Carrier Collection and Contact Selectivity in Solar Cells. Issue 20 (8th September 2019) - Rau, Uwe; Kirchartz, Thomas
Abstract: The electronic properties of the contacts to a photovoltaic absorber material are important for the final efficiency of any type of solar cell. For highly efficient solar cells based on high quality absorber materials like single‐crystalline silicon, polycrystalline Cu(In, Ga)Se2, CdTe, or metal‐halide perovskites, contact formation is even the decisive processing step determining the final efficiency. The present paper combines recently developed quantitative concepts for the description of contacts to solar cells in terms of their selectivity toward a more general description that is valid for all types of solar cells and all types of contacts. It is shown that the built‐in voltage is an important parameter to influence the selectivity of contacts to photovoltaic absorber materials. It is also shown that the contact selectivity is mathematically related to the collection efficiency which can be measured by luminescence based techniques. Abstract : Selectivity is a figure of merit for the usefulness of a contact in a photovoltaic device. Here, previous quantitative definitions of selectivity are compared and combined. The influence of the built‐in potential on the selectivity is investigated and it is illustrated how this quantity can be measured.